Practical Considerations in Adopting New Technology for Facial Cosmetic Procedures - Rousso, Joseph J. (Facial Plastic Surgery, 2020)
The field of facial plastic and reconstructive surgery encompasses both surgical and nonsurgical facets, creating a supplemental level of care and an additional layer of complexity. Determining the “best course of care” can be very difficult in experienced situations, but even more so when considering adopting an emerging technology. A basic and practical method of analyzing a new technology requires investigating the risk-to-benefit assessment, the utility and clinical outcomes compared with other treatment options, and an introspective ethical appraisal of whether the technology is foremost for patient care purposes. Even after employing a new technology, constant monitoring and reevaluation of the results is necessary to determine if it should be continued or altered.
Keywords: facial plastic surgery; emerging technologies; minimally invasive; facelift; face tightening